Determination of Dabigatran Concentration in Human Plasma and Breast Milk - F. Sidgwick; A. Porter; P. Ayuk; F. Kamali; A. Truemann (International Journal of Analytical Chemistry)
Venous thromboembolism (VTE) is an important cause of death following childbirth. Dabigatran etexilate can be a useful prophylaxis in susceptible women during the postpartum period. However, it is not clear whether dabigatran is excreted into breast milk in amounts which can be harmful to the suckling baby. We have developed an accurate, sensitive, and specific assay for the quantitation of dabigatran in both human plasma and breast milk. This is particularly useful for the determination of the extent by which dabigatran is secreted into breast milk in relation to its systemic availability. Dabigatran was enriched from both matrices using solid-phase extraction prior to separation on a C8-RPLC column and detection using SRM on a QqTrap mass spectrometer. The assay was validated for specificity, sensitivity, linearity, precision, accuracy, and stability of the analyte in human plasma and breast milk. The lower limit of detection for dabigatran was 20 pg/ml in plasma and 75 pg/ml in breast milk. This assay will aid future studies for the measurement of dabigatran concentrations in human breast milk to help determine if dabigatran etexilate can safely be administered to breast-feeding women.